Carbon-coated current collector as well as electrode and lithium ion battery applying carbon-coated current collector

By setting the carbon-coated insulating layers of the insulating region, transition region and conductive region in the carbon coating current collector of the lithium-ion battery, the problem of conductive carbon coating layer and insulating slurry string material is solved, and the peeling of the electrode active material layer is improved Force and battery cycling performance enhance the battery's safety performance and energy density.

CN119230842APending Publication Date: 2024-12-31YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411618453.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

During the processing of lithium-ion batteries, the conductive carbon coating layer slurry and the insulating slurry string lead to a decrease in safety protection performance of the insulating edges, and the contact between the electrode active material layer and the current collector substrate leads to a low peeling force, which affects the battery Cyclic performance.

Method used

Carbon coated current collector is used, wherein the carbon coated insulating layer includes an insulating region, a transition region and a conductive region. The insulating region and the conductive region are connected through the transition region. The insulating region is distributed on the side edges in the width direction of the carbon coated insulating layer to avoid electrode activity. The material layer penetrates down to the surface of the current collector substrate, forming a whole layer on the surface of the carbon-coated insulating layer, thereby increasing the peeling force between the electrode active material layer and the carbon-coated current collector.

Benefits of technology

The overall peeling force between the electrode active material layer and the carbon coated current collector is improved, the structural stability and cyclic performance of the electrochemical device are enhanced, the risk of short circuit caused by separator shrinkage is reduced, and the energy density and battery safety performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230842A_ABST
    Figure CN119230842A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-coated current collector, the carbon-coated current collector comprises a current collector base material and a carbon-coated insulating layer, the carbon-coated insulating layer is arranged on the surface of the current collector base material, the carbon-coated insulating layer comprises an insulating region, a transition region and a conductive region, materials forming the insulating region comprise inorganic insulating particles, materials forming the conductive region comprise conductive particles, and the inorganic insulating particles are arranged in the transition region. Materials forming the transition region comprise inorganic insulating particles and conductive particles; the insulation areas are distributed on the edges of the two sides of the carbon-coated insulation layer in the width direction, the conductive areas are distributed between the insulation areas arranged on the opposite sides, the insulation areas and the conductive areas are connected through transition areas, and the width of the transition areas is smaller than or equal to 10 mm; the thickness of the insulating region is 0.5-2 microns, the thickness of the transition region is 1-4 microns, and the thickness of the conductive region is 0.5-2 microns. The arrangement of the carbon-coated insulating layer can effectively reduce the condition of powder falling of the electrode active material layer compounded with the carbon-coated current collector, improve the structural stability of the electrochemical device using the carbon-coated current collector, and realize the improvement of the cycle performance of the electrochemical device. In the carbon-coated insulating layer, the energy density of the electrochemical device using the carbon-coated current collector can be improved due to the arrangement of the conductive region, and the electrochemical device using the carbon-coated current collector can be safely protected due to the arrangement of the insulating region. The arrangement of the transition area not only can realize clear division of the insulation area and the conductive area, but also can enable the subarea coated with the carbon insulation layer to keep better compactness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular, relates to a carbon-coated current collector and an electrode and a lithium ion battery using the same. Background Art

[0002] Lithium-ion battery technology has become a hotly developed technology field in recent years due to its advantages such as high energy density, long cycle life, and green environmental protection. Energy density and safety performance are two important performance indicators of lithium-ion batteries. In order to improve the energy density of lithium-ion batteries and improve the safety performance of lithium-ion batteries, researchers in the field of lithium-ion batteries have made many attempts in the design of lithium-ion batteries. In order to improve the energy density of lithium-ion batteries, a carbon coating layer is usually set between the electrode active coating and the current collector in this field. In order to improve the safety performance of lithium-ion batteries, an insulating slurry can be applied to the edge of the current collector to form an insulating edge, thereby preventing the battery cell from thermally shrinking the diaphragm under high temperature conditions, effectively reducing the risk of short circuit caused by contact between the positive and negative electrodes due to diaphragm shrinkage.

[0003] At present, there are related technical reports on setting an insulating edge and a carbon coating layer on the surface of a current collector at the same time. However, during the processing of lithium-ion batteries with an insulating edge set on the edge of the current collector, the conductive carbon coating slurry or the electrode active material slurry often mixes with the insulating slurry, which causes the conductive material to penetrate and diffuse in the insulating slurry, and the formed insulating edge is doped with conductive materials, which reduces the safety protection performance of the insulating edge.

[0004] In order to avoid the insulation slurry and the conductive electrode active material slurry or carbon coating slurry from mixing with each other, the common processing method in the prior art is to first complete the interval coating of the insulation slurry and the carbon coating slurry to form a gap between the formed insulation edge and the carbon coating layer, and then coat the electrode active material slurry on the surface of the carbon coating layer. The electrode active material slurry will penetrate into the gap between the insulation edge and the carbon coating layer, and the electrode active material slurry will be dried to form an electrode active coating. However, the pole piece obtained in this way often has the problem of low peeling force between the active material layer and the current collector and easy powder loss of the electrode active material layer. The use of such pole pieces will reduce the cycle performance of lithium-ion batteries. Summary of the invention

[0005] In order to take into account the safety performance, energy density and cycle performance of lithium-ion batteries, the present invention provides a carbon-coated current collector and an electrode and a lithium-ion battery using the same.

[0006] According to one aspect of the present invention, a carbon-coated current collector is provided, which includes a current collector substrate and a carbon-coated insulating layer, the carbon-coated insulating layer is arranged on the surface of the current collector substrate, the carbon-coated insulating layer includes an insulating region, a transition region and a conductive region, the material constituting the insulating region includes inorganic insulating particles, the material constituting the conductive region includes conductive particles, and the material constituting the transition region includes inorganic insulating particles and conductive particles; in the width direction of the carbon-coated insulating layer, the insulating region, the transition region and the conductive region are arranged in sequence, the insulating region and the conductive region are connected by the transition region, and the insulating region is distributed on at least one side edge of the carbon-coated insulating layer in the width direction.

[0007] In the present invention, the "current collector substrate" involved refers to various types of current collector substrates suitable for lithium batteries, such as metal aluminum foil, metal copper foil, composite aluminum foil, composite copper foil, etc.

[0008] In the carbon-coated current collector provided by the present invention, the carbon-coated insulating layer is a continuously distributed coating, and the insulating area and the conductive area are connected by a transition area. When it is necessary to further form an electrode active material layer on the surface of the carbon-coated current collector, the electrode active material slurry is coated on the surface of the carbon-coated insulating layer. Under the blocking effect of the carbon-coated insulating area, the electrode active material slurry will not penetrate into the surface of the current collector substrate, and the formed electrode active material layer will be stacked on the surface of the carbon-coated insulating layer as a whole, and will not form a composite interface in which the electrode active material layer is in direct contact with the empty foil of the current collector substrate, thereby avoiding the problem of large regional differences in the peeling force of the composite interface caused by the electrode active material layer being simultaneously compounded with the empty foil and the conductive area of ​​the current collector substrate with significant material differences, promoting uniform compounding between the electrode active material layer and the carbon-coated current collector, thereby improving the overall peeling force between the electrode active material layer and the carbon-coated current collector. In summary, the provision of the carbon-coated insulating layer can effectively reduce the powdering of the electrode active material layer compounded with the carbon-coated current collector, improve the structural stability of the electrochemical device using the carbon-coated current collector, and achieve the improvement of the cycle performance of the electrochemical device. The provision of the conductive area can also improve the energy density of the electrochemical device using the carbon-coated current collector, and improve the peeling force between the electrode active material layer formed on the surface of the carbon-coated current collector and the composite current collector, thereby reducing the internal resistance of the battery cell, increasing the battery cell rate, and improving the battery cycle performance of the electrochemical device using the composite current collector. The provision of the insulating area effectively reduces the risk of short circuit caused by the positive and negative electrodes coming into contact due to the shrinkage of the diaphragm, and plays a safety protection role for the electrochemical device using the carbon-coated current collector.

[0009] Preferably, the transition zone includes a first region and a second region which are stacked, the material constituting the first region includes conductive particles, the material constituting the second region includes inorganic insulating particles, and the bottom surface of the first region of the transition zone contacts the surface of the current collector substrate. In the above scheme, by dividing the transition zone into a layered arrangement of the first region and the second region, the transition zone directly compounds with the current collector substrate with the first region containing the conductive particles, which is conducive to improving the interlayer peeling force between the transition zone and the current collector substrate.

[0010] Preferably, the conductive particles are carbon material particles, such as one or more of conductive carbon black, graphite, acetylene black, carbon nanotubes, doped carbon nanotubes, carbon fibers, graphene, silver particles, gold particles, copper particles, and aluminum particles; the inorganic insulating particles are various insulating materials suitable for lithium batteries, such as one or more of aluminum oxide, boehmite, calcium oxide, silicon carbide, silicon dioxide, aluminum oxide, boron nitride, magnesium oxide, zirconium oxide, and barium titanate.

[0011] Preferably, in the carbon-coated insulating layer, the thickness of the first region shows a decreasing trend in the direction away from the conductive region, and the thickness of the second region shows an increasing trend in the direction away from the conductive region. The thickness change trends of the first region and the second region are opposite, and the two cooperate with each other to maintain good consistency in the thickness of the transition zone, which is conducive to the subsequent smooth coating of the electrode active material slurry on the surface of the carbon-coated current collector, and can improve the flatness of the pole piece thus obtained, avoid the formation of structural weaknesses based on the concave-convex defects of the pole piece surface, and thus improve the cycle performance of the electrochemical device using the pole piece. In addition, the thickness of the first region and the second region has a gradual trend, so that the first region and the second region are compounded through the inclined surface, the contact area between the first region and the second region is increased, and the interface bonding force is increased, which is conducive to the stable compounding of the two, and the structural stability of the transition zone and the carbon-coated current collector is improved. The angle can be selected according to the width of the transition zone. The selection rule is that the narrower the transition zone, the larger the angle, and the contact area between the first region and the second region can be increased.

[0012] Preferably, the interface where the first region contacts the second region has an angle of inclination of 1°-10° relative to the surface of the current collector substrate. The above-mentioned inclination angle refers to the angle between the plane formed by each point on the composite interface between the first region and the second region and the surface of the current collector substrate in the carbon-coated insulating layer formed on the surface of the current collector substrate after the slurry used to form the carbon-coated insulating layer is completely dried. The first region and the second region are composited according to the above-mentioned inclination angle range, so that the inorganic insulating particles on the lower surface of the second region (close to the inclined surface of the current collector substrate) can be evenly and stably dispersed on the upper surface of the first region, so as to improve the mutual adhesion between the first region and the second region and strengthen the composite interface stability between the first region and the second region.

[0013] Preferably, the average particle size D of the inorganic insulating particles included in the carbon-coated insulating layer is 50 = 0.1 μm-5 μm, the average particle size D of the conductive particles included in the carbon-coated insulating layer 50 =0.05μm-10μm. By adjusting the particle sizes of the inorganic insulating particles and the conductive particles in the carbon-coated insulating layer to the above range, it is beneficial to improve the interlayer peeling force between the carbon-coated insulating layer and the current collector substrate, and to improve the interlayer peeling force between the carbon-coated current collector and the electrode active material layer.

[0014] Preferably, the average particle size D of the inorganic insulating particles included in the carbon-coated insulating layer is 50 = 0.6 μm-1 μm, the average particle size D of the conductive particles included in the carbon-coated insulating layer 50 =0.05μm-2μm.

[0015] Preferably, the ratio of the average particle size of the conductive particles to the average particle size of the inorganic insulating particles is 1:(0.4-0.8). In order to optimize the safety and structural stability of the carbon-coated current collector, the sizes of the conductive particles and the inorganic insulating particles meet the above ratio. On the one hand, the inorganic insulating particles located at the composite interface between the first region and the second region can be better filled between the conductive particles, thereby enhancing the interlayer bonding force between the first region and the second region, which not only ensures the hardness and strength of the transition layer, but also improves the toughness and impact resistance of the transition layer. On the other hand, since the inorganic insulating particles are smaller than the conductive particles, it is beneficial to improve the heat dissipation effect of the transition layer, and the pores of the first region composed of the inorganic insulating particles are smaller, so that the first region has a relatively dense structural feature, thereby ensuring that the first region composed of the inorganic insulating particles will cover the conductive particles constituting the second region, thereby ensuring the insulating effect of the insulating layer. In addition, based on the angle range of the inclination angle of the interface between the first region and the second region relative to the surface of the current collector substrate, the ratio of the average particle size of the conductive particles to the average particle size of the inorganic insulating particles is further adjusted to the above range, so that when the inclination angle and the particle size are optimally combined, the preferred inclination angle can optimize the stress distribution, and the preferred particle size combination can improve the density and crack resistance of the material, thereby achieving the effect of significantly improving the strength, toughness and wear resistance of the carbon-coated insulating layer. In addition, the inclination angle and particle size combination can synergistically form a dense protective layer to prevent the penetration of corrosive media in the transition layer, thereby improving the corrosion resistance of the transition layer and avoiding failure of the insulation function.

[0016] Preferably, in the width direction of the carbon-coated current collector, 0 mm < width of the transition zone ≤ 10 mm. The present invention limits the width of the transition zone to a range of no more than 10 mm, which can not only achieve a clear division between the insulating zone and the conductive zone, so that the insulating zone and the conductive zone can play their roles normally, but also keep the partitions of the carbon-coated insulating layer relatively compact, avoiding the situation where the current collector is too large and is difficult to be placed in the battery shell later or is easily squeezed and damaged during the shell insertion process.

[0017] Preferably, the width of the transition zone is 1 mm-10 mm.

[0018] Preferably, the thickness of the insulating region is 0.5 μm-100 μm. Preferably, the thickness of the insulating region is 0.5 μm-2 μm.

[0019] Preferably, the thickness of the transition zone is 0.2 μm-105 μm.

[0020] Preferably, the thickness of the conductive area is 0.2 μm-5 μm. Preferably, the thickness of the conductive area is 0.5 μm-2 μm.

[0021] Preferably, the thickness of the transition region, the insulating region and the conductive region are the same, thereby reducing the occurrence of wrinkles and other undesirable conditions on the current collector substrate during subsequent electrode processing.

[0022] According to the second aspect of the present invention, a method for preparing a carbon-coated current collector as described above is provided, comprising the following operations: S1. coating a conductive material slurry containing conductive particles on any surface of the current collector substrate; S2. drying the conductive material slurry to form a conductive material coating; S3. coating an inorganic material slurry containing inorganic insulating particles on the edge of the conductive material coating along the extension direction of the current collector substrate, and allowing the inorganic material slurry to cover the edge of the conductive material coating and the surface area of ​​the current collector substrate adjacent to the edge; S4. drying the inorganic material slurry to form a carbon-coated insulating layer on the surface of the current collector substrate. The method uses a step-by-step coating and step-by-step drying method to complete the distribution of carbon material slurry and inorganic ceramic slurry on the surface of the current collector substrate, thereby in the carbon-coated insulating layer formed on the surface of the current collector substrate, the distribution of carbon material and inorganic ceramic particles is clearly divided, and no cross-contamination occurs, ensuring that the conductive area and the insulating area can fully play their respective roles.

[0023] Preferably, S1 also includes the following operations: completing the coating of the conductive material slurry in a zoned coating manner, the corresponding coating area is divided into a main body area and two side edge areas arranged in the width direction of the main body area, and in the process of coating the conductive material slurry, controlling the coating amount of the conductive material slurry so that the coating thickness of the corresponding main body area is greater than the coating thickness of the corresponding edge area. In order to make the coating formed by the conductive material slurry meet the above-mentioned characteristics: for example, a scraper with a specific shape is used to complete the coating of the above-mentioned conductive material slurry, and the shape of the scraper used satisfies that the length of the scraper edge area is less than the length of the scraper main body area, and the direction perpendicular to the plane where the conductive material slurry coating is located is the length direction of the scraper; for example, the coating of the above-mentioned conductive material slurry can be completed by using a coating roller with a specific shape, and the coating roller used is provided with a plurality of holes for applying the conductive material slurry, and the distribution of the holes within a certain area close to the edge of the coating roller satisfies that the hole diameter located at the edge of the coating roller is smaller than the hole diameter located in the middle of the coating roller. On this basis, according to actual needs, the shape of the conductive material slurry coating can be further regulated by adjusting the interval between adjacent holes.

[0024] Preferably, the above preparation method is specifically implemented according to process I: the current collector substrate to be coated is installed in the coating device, the current collector substrate is unwound, and then the current collector substrate is passed through the pulling mechanism to reach the coating operation area, and a conductive material slurry containing conductive particles is coated on the first surface of the current collector substrate, and then the current collector substrate coated with the conductive material slurry enters the oven to dry the conductive material slurry, thereby forming a conductive material coating on the first surface of the current collector substrate; then the first surface of the current collector substrate is coated with an inorganic material slurry, and then the current collector substrate coated with the inorganic material slurry enters the oven to dry the inorganic material slurry, thereby forming a carbon-coated insulating layer on the first surface of the current collector substrate; referring to the aforementioned carbon-coated insulating layer forming operation on the first surface of the current collector substrate, the same operation is performed on the second surface of the current collector substrate that is arranged opposite to the first surface, so as to form a carbon-coated insulating layer on the second surface of the current collector substrate, and finally the finished product is rolled up.

[0025] Preferably, the preparation method is specifically implemented according to process II: the current collector substrate to be coated is installed in the coating device, the current collector substrate is unwound by unwinding, and then the current collector substrate is passed through the pulling mechanism to reach the coating operation area, and a conductive material slurry containing a conductive material is coated on the first surface of the current collector substrate, and then the current collector substrate coated with the conductive material slurry enters the oven to dry the conductive material slurry, thereby forming a conductive material coating on the first surface of the current collector substrate; referring to the aforementioned carbon material coating forming operation on the first surface of the current collector substrate, the same operation is performed on the second surface of the current collector substrate that is arranged opposite to the first surface, so as to form a conductive material coating on the first surface of the current collector substrate. A conductive material coating is formed on the second surface of the fluid substrate to obtain a semi-finished product, which is then rolled up; the semi-finished product is then coated a second time by first coating the first surface of the current collector substrate with an inorganic material slurry, and then allowing the current collector substrate coated with the inorganic material slurry to enter an oven to dry the inorganic material slurry, thereby forming a carbon-coated insulating layer on the first surface of the current collector substrate; then, referring to the aforementioned inorganic material slurry coating and drying operations on the first surface of the current collector substrate, the same operations are performed on the second surface of the current collector substrate that is arranged opposite to the first surface, so as to form a carbon-coated insulating layer on the second surface of the current collector substrate, and finally the finished product is rolled up.

[0026] According to the third aspect of the present invention, there is provided an electrode, which includes the carbon-coated current collector and an electrode active material layer as described above, wherein the electrode active material layer is arranged on the surface of the carbon-coated insulating layer, and the electrode active material layer covers the conductive area. The electrode provided by the present invention has good structural stability, and the electrode active material layer can be stably compounded with the carbon-coated current collector. Under normal storage and use conditions, it is not easy for the electrode active material layer to fall off or peel off from the carbon-coated current collector. As electrode active materials applicable to the present invention, the positive electrode active material can be selected from various types of positive electrode active materials applicable to lithium batteries such as lithium iron phosphate and ternary materials, and the negative electrode active material can be selected from various types of negative electrode active materials applicable to lithium batteries such as graphite and silicon-carbon materials.

[0027] According to a fourth aspect of the present invention, a battery is provided, comprising the electrode as described above. The battery has good safety performance, energy density and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 A schematic diagram of the structure of a scraper used for coating a conductive material slurry in Example 1;

[0029] Figure 2 Schematic diagram of the structure of the positive electrode sheet prepared in Example 1, wherein: Figure 2The inner figure in the figure is an enlarged schematic diagram of the transition zone, and the dotted lines in the figure are auxiliary lines for clearly showing the various partitions involved in the positive electrode sheet. The "θ" marked in the figure refers to the inclined angle formed by the interface where the first area and the second area in the transition zone contact with each other and the surface of the current collector substrate;

[0030] Figure 3 The structure diagram of the positive electrode sheet prepared in Example 5, wherein: Figure 3 The inner figure in the figure is an enlarged schematic diagram of the transition zone, and the dotted lines in the figure are auxiliary lines for clearly showing the various partitions involved in the positive electrode sheet. The "θ" marked in the figure refers to the inclined angle formed by the interface where the first area and the second area in the transition zone contact with each other and the surface of the current collector substrate;

[0031] Figure 4 This is a schematic diagram of the structure of the positive electrode sheet prepared in Comparative Example 1;

[0032] Figure 5 This is a schematic diagram of the structure of the positive electrode sheet prepared in Comparative Example 2. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.

[0034] Example 1

[0035] 1. Preparation of positive electrode sheet:

[0036] (1) Slurry preparation

[0037] Preparation of conductive material slurry: Calculated by mass, 15 parts of conductive particles (consisting of 10 parts of conductive carbon black and 5 parts of graphite KS-6), 100 parts of deionized water, and 20 parts of polypropylene binder are mixed, and the resulting mixed slurry is mechanically stirred (stirring speed is 1000 rpm) until uniform, thereby obtaining a pre-dispersed carbon slurry. The pre-dispersed carbon slurry is sand-milled with a sand mill at 10°C for 2 hours, and the conductive material slurry is obtained.

[0038] Preparation of inorganic material slurry: Calculated by mass, 20 parts of inorganic insulating particles (the inorganic material used in this embodiment is silicon carbide), 10 parts of polypropylene binder, 1 part of polyethylene glycol and 69 parts of solvent NN-dimethylformamide are mixed, and the resulting mixed slurry is dispersed uniformly under high-speed stirring, and the material is discharged to obtain inorganic material slurry.

[0039] (2) Preparation of carbon-coated current collector:

[0040] S1. Using aluminum foil as the current collector substrate, the current collector substrate to be coated is installed in the coating device, the current collector substrate is unwound by unwinding, and then the current collector substrate passes through the pulling mechanism to reach the coating operation area, and the conductive material slurry is coated on the first surface of the current collector substrate by using the micro-concave roller coating technology, such as Figure 1 As shown, the conductive material slurry is applied by using a scraper 2 whose edge 2-1 is inclined at a certain angle to apply a conductive material slurry coating on the first surface of the current collector substrate, and the shape formed by the conductive material slurry coating after drying is controlled by the inclined angle of the edge 2-1 of the scraper 2.

[0041] S2. Then, the current collector substrate coated with the conductive material slurry is placed in an oven and dried at 150° C. for 5 minutes to dry the conductive material slurry, thereby forming a conductive material coating on the first surface of the current collector substrate. Based on the scraper shape used in S1, the conductive material coating prepared in this embodiment is inclined relative to the current collector substrate at the width edge, and the inclination angle θ=4°;

[0042] S3. Then the first surface of the current collector substrate is coated with an inorganic material slurry, and the coating area overlaps with the edge of the conductive material coating;

[0043] S4. Then the current collector substrate coated with the inorganic material slurry is put into an oven to dry the inorganic material slurry, thereby forming a carbon-coated insulating layer on the first surface of the current collector substrate;

[0044] S5. Referring to the aforementioned operation of forming the carbon-coated insulating layer on the first surface of the current collector substrate, the same operation is performed on the second surface of the current collector substrate that is arranged opposite to the first surface to form a carbon-coated insulating layer on the second surface of the current collector substrate, and finally the finished product is rolled up.

[0045] (2) Preparation of positive electrode active coating

[0046] LiNi 0.6 Mn 0.2 Co 0.2 O 2 (NCM622), conductive agent CNT and SP, binder PVDF and dispersant are uniformly dispersed in solvent NMP (N-methylpyrrolidone) in a mass ratio of 96.8%: 1.0%: 1.0%: 1.0%: 0.2% to obtain a positive electrode slurry with a solid content of 76%. The positive electrode active material contained in the positive electrode active slurry is LiNi 0.6 Mn 0.2 Co 0.2 O 2 (NCM622), coating the above-mentioned positive electrode active slurry on the surface of the carbon-coated current collector prepared above, and forming a positive electrode active material layer with NCM622 as the positive electrode active material on the surface of the carbon-coated current collector.

[0047] The positive electrode sheet thus prepared has the following structural characteristics (such as Figure 2 ):

[0048] The positive electrode sheet is composed of a carbon-coated current collector and a positive electrode active material layer 1-3 arranged on the surface of the carbon-coated current collector, wherein the carbon-coated current collector includes a current collector substrate 1-2 and a carbon-coated insulating layer 1-1, and the carbon-coated insulating layer 1-1 is arranged on the surface of the current collector substrate 1-2. The carbon-coated insulating layer 1-1 includes an insulating region, a transition region and a conductive region 1-15. In the thickness direction of the carbon-coated insulating layer 1-1, the region composed only of inorganic material particles is the insulating region, the region composed only of conductive material is the conductive region 1-15, and the region including both inorganic material particles and conductive material is the transition region. In the carbon-coated insulating layer 1-1, the insulating regions are distributed on the two side edges of the carbon-coated insulating layer 1-1 in the width direction, the conductive region 1-15 is distributed between the insulating regions arranged on the opposite sides, and the insulating region and the conductive region 1-15 are connected by the transition region. Figure 2 As shown, the formed carbon-coated insulating layer 1-1 includes two insulating regions and two transition regions. For the convenience of marking, the two insulating regions are marked as the first insulating region 1-11 and the second insulating region 1-12, and the two transition regions are marked as the first transition region 1-13 and the second transition region 1-14. In the width direction of the carbon-coated insulating layer 1-1, the first insulating region 1-11, the first transition region 1-13, the conductive region 1-15, the second transition region 1-14, and the second insulating region 1-12 are connected in sequence. In the transition region, the region composed of conductive material is the first region 1-16, and the region composed of inorganic ceramic particles is the second region 1-17. The first region 1-16 is located at the bottom of the second region 1-17. The interface between the first region 1-16 and the second region 1-17 forms an inclined angle θ=4° with the surface of the current collector substrate.

[0049] In the above processing, the particle size distribution of the conductive particles used meets D 50 The particle size distribution of the inorganic insulating particles used meets D 50 In the carbon-coated current collector prepared in this embodiment: the width of the carbon-coated insulating layer 1-1 is 800 mm; the width of the conductive region 1-15 is 780 mm, and the thickness is 2 μm; the width of the first insulating region 1-11 and the second insulating region 1-12 are 5 mm, and the thickness is 2 μm; the width of the first transition region 1-13 and the second transition region 1-14 are 5 mm, and the thickness of the first transition region 1-13 and the second transition region 1-14 are 2 μm, respectively.

[0050] 2. Preparation of negative electrode

[0051] Copper foil is used as the negative electrode current collector, and artificial graphite is used as the negative electrode active material to prepare the negative electrode active material layer.

[0052] 3. Selection of diaphragm

[0053] Alumina ceramic-coated polyethylene separator is used as a separator for assembling lithium-ion batteries.

[0054] 4. Preparation of electrolyte

[0055] Take propylene carbonate, ethylene carbonate, and ethyl methyl carbonate and mix them in a mass ratio of 1:1:1 to obtain a carbonate solvent, and add LiPF 6 , prepared to 1 mol·L -1 LiPF 6 A carbonate solution is prepared and the carbonate solution is used as an electrolyte for a lithium ion battery.

[0056] 5. Assembly of lithium-ion batteries

[0057] The positive electrode sheet, isolation film and negative electrode sheet prepared above are stacked in order to prepare a bare battery cell; the bare battery cell is placed in an outer packaging shell of a lithium battery, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0058] Example 2

[0059] This embodiment refers to the method for preparing a lithium-ion battery in Example 1 to prepare a lithium-ion battery. This embodiment uses the tilt angle θ (hereinafter referred to as "tilt angle θ") formed by the interface where the first region 1-16 and the second region 1-17 in the transition zone provided by the carbon-coated current collector are in contact with the surface of the current collector substrate as a variable, and sets different treatment groups to prepare lithium-ion batteries. The difference between different treatment groups in the process of preparing lithium-ion batteries lies in the different shapes of scrapers used in S1 for preparing the carbon-coated current collector. Different shapes of scrapers are used to adjust the tilt angle θ formed by the interface where the first region 1-16 and the second region 1-17 in contact with the transition zone provided by the carbon-coated current collector in different treatment groups and the surface of the current collector substrate. Based on the above differences, the treatment groups set in this embodiment and the corresponding tilt angle θ are shown in Table 1, wherein the scrapers used by each treatment group in this embodiment to prepare the carbon-coated current collector are scrapers with a certain tilt angle at the edge. In order to clearly show the differences between the treatment groups in this embodiment and those in Embodiment 1, the tilt angles θ corresponding to the carbon-coated current collectors prepared in Embodiment 1 are also shown in Table 1.

[0060] Table 1. Related numbers and corresponding variables of the treatment groups set in Example 2

[0061] Group Tilt angle θ Example 1 4° Example 2 Treatment Group 1 1° Example 2 Treatment Group 2 7° Example 2 Treatment Group 3 10° Example 2 Treatment Group 4 11° Example 2 Treatment Group 5 0.5°

[0062] In addition to the above differences, the other materials and process operations used in preparing lithium-ion batteries in all treatment groups set in this embodiment are strictly consistent with those in Example 1. Therefore, in this embodiment, the structure of the positive electrode sheet prepared by each treatment group is similar to that of the positive electrode sheet prepared in Example 1.

[0063] Example 3

[0064] This embodiment refers to the method for preparing a lithium ion battery in Example 1 to prepare a lithium ion battery. In this embodiment, the inclined angle θ (hereinafter referred to as "inclined angle θ") formed by the interface between the first region 1-16 and the second region 1-17 in the transition zone provided in the carbon-coated current collector and the surface of the current collector substrate and the conductive particles and inorganic insulating particles used to prepare the carbon-coated current collector are used. 50 The ratio of is used as a variable, and different treatment groups are set to prepare lithium-ion batteries. The group with the same tilt angle θ in the prepared carbon-coated current collector is used as a control. The relationship between each treatment group in this embodiment and its respective control treatment group is as follows: Treatment group 1 of Example 3 is a control with Example 1, and the tilt angle θ is 4°; Treatment group 2 of Example 3 is a control with treatment group 1 of Example 2, and the tilt angle θ is 1°; Treatment group 3 of Example 3 is a control with treatment group 4 of Example 2, and the tilt angle θ is 11°; Treatment group 4 of Example 3 is a control with treatment group 5 of Example 2, and the tilt angle θ is 0.5°. The treatment groups set in this embodiment and the corresponding tilt angle θ, the particle size of the conductive particles and inorganic insulating particles used are shown in Table 2. In order to clearly show the difference between each treatment group in this embodiment and the control treatment group, the tilt angle θ corresponding to the carbon-coated current collector prepared in Example 1, Treatment group 1 of Example 2, Treatment group 4 of Example 2, and Treatment group 5 of Example 2, and the D of the conductive particles and inorganic insulating particles used in Example 1 are shown in Table 2. 50 The ratios are shown in Table 2.

[0065] Table 2. Related numbers and corresponding variables of the treatment groups set in Example 3

[0066]

[0067]

[0068] Except for the above differences, other materials and process operations used in preparing lithium-ion batteries in all treatment groups set in this embodiment are strictly consistent with those in Example 1.

[0069] Example 4

[0070] This example prepares a lithium-ion battery by referring to the method for preparing a lithium-ion battery in Example 1. This example uses the particle size of the conductive particles and inorganic insulating particles used as variables to set different treatment groups to prepare lithium-ion batteries. The treatment groups set in this example and the corresponding particle sizes of the conductive particles and inorganic insulating particles used are shown in Table 3. In order to clearly show the difference between each treatment group in this example and that in Example 1, the particle sizes of the conductive particles and inorganic insulating particles used in Example 1 are also shown in Table 3. Among the treatment groups set in this example, the D of the conductive particles and inorganic insulating particles used in Treatment Group 5 and Treatment Group 6 is 2.34×10·m3 / cm2. 50 The ratio is basically the same as that of the conductive particles and inorganic insulating particles used in the embodiment. 50 The ratio is the same.

[0071] Table 3. Related numbers and corresponding variables of the treatment groups set in Example 4

[0072] Group <![CDATA[Conductive particle D 50 / μm]]> <![CDATA[Inorganic insulating particle D 50 / μm]]> Example 1 1 0.6 Example 4 Treatment Group 1 1 0.4 Example 4 Treatment Group 2 1 0.8 Example 4 Treatment Group 3 1 0.2 Example 4 Treatment Group 4 1 0.9 Example 4 Treatment Group 5 0.83 0.5 Example 4 Treatment Group 6 2 1.2 Example 4 Treatment Group 7 0.6 1

[0073] Except for the above differences, other materials and process operations used in preparing lithium-ion batteries in all treatment groups set in this embodiment are strictly consistent with those in Example 1.

[0074] Example 5

[0075] This example prepares a lithium ion battery by referring to the method for preparing a lithium ion battery in Example 1.

[0076] In the process of preparing the lithium ion battery in this embodiment, the difference from the embodiment 1 is that the process of preparing the carbon-coated current collector is adjusted to:

[0077] S1. Using aluminum foil as the current collector substrate, the current collector substrate to be coated is installed in the coating device, the current collector substrate is unwound by unwinding, and then the current collector substrate is passed through the pulling mechanism to reach the coating operation area, and the inorganic material slurry is coated on the first surface of the current collector substrate by using the micro-concave roller coating technology to apply the inorganic material slurry coating on the first surface of the current collector substrate.

[0078] S2. Then the current collector substrate coated with the inorganic material slurry enters an oven to dry the inorganic material slurry, thereby forming an insulating material coating on the first surface of the current collector substrate;

[0079] S3. Then coating the first surface of the current collector substrate with a conductive material slurry, wherein the coating area overlaps with the inner edge of the insulating material coating;

[0080] S4. Then the current collector substrate coated with the conductive material slurry is placed in an oven and dried at 150°C for 5 minutes to dry the conductive material slurry, thereby forming a carbon-coated insulating layer on the first surface of the current collector substrate;

[0081] S5. Referring to the aforementioned operation of forming the carbon-coated insulating layer on the first surface of the current collector substrate, the same operation is performed on the second surface of the current collector substrate that is arranged opposite to the first surface to form a carbon-coated insulating layer on the second surface of the current collector substrate, and finally the finished product is rolled up.

[0082] Except for the above differences, other specific operations for preparing the lithium-ion battery in this embodiment are strictly consistent with those in Embodiment 1.

[0083] Based on the above differences, the difference between the carbon-coated current collector prepared in this embodiment and the carbon-coated current collector prepared in Example 1 is that in the first transition zone 1-13 and the second transition zone 1-14 of the carbon-coated current collector prepared in this embodiment, the area composed of the conductive material is the first area 1-16, and the area composed of the inorganic ceramic particles is the second area 1-17, and the second area 1-17 is located at the bottom of the first area 1-16, such as Figure 3 shown.

[0084] Comparative Example 1

[0085] In this comparative example, a lithium ion battery was prepared by referring to the method for preparing a lithium ion battery in Example 1.

[0086] The difference from Example 1 is that in the process of preparing the carbon-coated current collector in this comparative example, a gap is formed between the area coated with the carbon material slurry and the area coated with the inorganic ceramic slurry.

[0087] Based on the above differences, compared with the positive electrode sheet prepared in Example 1, the positive electrode sheet prepared in this comparative example has the following distinguishing features: Figure 4 As shown, the first insulating region 1-11, the conductive region 1-15, and the second insulating region 1-12 are arranged in sequence, and the positive electrode active material slurry penetrates into the gap between the conductive region 1-15 and the first insulating region 1-11 and the second insulating region 1-12. The positive electrode active material layer 1-3 formed thereby is in direct contact with the conductive region 1-15 and also in direct contact with the empty foil of the current collector substrate 1-2.

[0088] Except for the above differences, other specific operations for preparing the lithium-ion battery in this comparative example are strictly consistent with those in Example 1.

[0089] Comparative Example 2

[0090] In this comparative example, a lithium ion battery was prepared by referring to the method for preparing a lithium ion battery in Example 1.

[0091] The difference from Example 1 is that in the process of preparing the carbon-coated current collector in this comparative example, the area coated with the carbon material slurry is adjacent to the area coated with the inorganic ceramic slurry.

[0092] Based on the above differences, compared with the positive electrode sheet prepared in Example 1, the carbon-coated current collector prepared in this comparative example has the following distinguishing features: Figure 5 As shown, the first insulating region 1-11, the conductive region 1-15, and the second insulating region 1-12 are adjacent to each other in sequence, and there is no transition zone between the insulating region (the first insulating region 1-11 or the second insulating region 1-12) and the conductive region 1-15. The positive electrode active material slurry is laid on the upper surfaces of the first insulating region 1-11, the conductive region 1-15, and the second insulating region 1-12, and the positive electrode active material layer 1-3 formed thereby is simultaneously compounded with the upper surfaces of the first insulating region 1-11, the conductive region 1-15, and the second insulating region 1-12.

[0093] Except for the above differences, other specific operations for preparing the lithium-ion battery in this comparative example are strictly consistent with those in Example 1.

[0094] Test Case

[0095] 1. Test subjects

[0096] The pole pieces and lithium-ion batteries prepared in Examples 1-5 and Comparative Examples 1 and 2 were used as test objects in this test example.

[0097] 2. Test items

[0098] (1) Lithium-ion battery cycle performance test: In an environment of 25°C, the first charge and discharge are performed, constant current and constant voltage charging is performed at a charging current of 0.5C until the upper limit voltage is 4.25V, and then constant current discharge is performed at a discharge current of 1C until the final voltage is 2.75V, and the discharge capacity of the first cycle is recorded. After that, the above steps are repeated for 400 charge and discharge cycles, and the discharge capacity of the 400th cycle is recorded. Cycle capacity retention rate = (discharge capacity of the 400th cycle / discharge capacity of the first cycle) × 100%.

[0099] (2) Lithium-ion battery safety performance test: The lithium-ion battery is charged at a current of 0.5C to an upper voltage limit of 4.25V, and then charged at a constant voltage at the corresponding cut-off voltage, with a cut-off current of 0.05C. A steel needle with a diameter of 3mm is used to completely penetrate the center of the battery at a speed of 50mm / s, and the penetration state is maintained for 1 hour or when thermal runaway occurs and the battery surface temperature drops to 50℃, the test is terminated.

[0100] (3) Lithium-ion battery rate performance test: Take the lithium-ion battery and place it at a test temperature of 25°C for 5 minutes, then charge the lithium-ion battery with a constant current of 1C to the designed full charge voltage, and then charge it with a constant voltage of 0.05C (cut-off current) at the designed full charge voltage; take the lithium-ion battery and place it at a test temperature of 25°C for 5 minutes, then discharge it with a constant current of 1C to 2.75V, and record the 1C discharge capacity; then place it at a test temperature of 25°C for 30 minutes, take the lithium-ion battery and place it at a test temperature of 25°C for 5 minutes, then charge the lithium-ion battery with a constant current of 2C to the designed full charge voltage, and then charge it with a constant voltage of 0.05C (cut-off current) at the designed full charge voltage; place it at a test temperature of 25°C for 30 minutes, then discharge it with a constant current of 2C to 2.75V, and record the 2C discharge capacity; then place it at a test temperature of 30 minutes. Rate performance = 2C discharge capacity / 1C discharge capacity × 100%.

[0101] (4) Positive electrode stripping force test: First, use a flat paper cutter to cut the rolled positive electrode into strips with a length of 170 mm and a width of 30 mm; then wipe the scaleless steel ruler clean to leave no stains or dust; then, stick a 60 mm wide transparent tape horizontally on the bottom of the dried scaleless steel ruler with the end faces flush; then, stick a 25 mm wide double-sided tape on the transparent tape with the same length as the width of the transparent tape and centered; finally, stick the test sample on the double-sided tape with the end faces flush, and use a 84 mm diameter and 45 mm high pressure wheel (2 kg) to roll back and forth on the surface of the electrode twice. Fix the free end of the electrode to the upper mold of the tensile tester, and fix the bottom end of the stainless steel plate to the lower mold of the tensile tester. Start the tensile tester and perform a 180° peeling test at a peeling speed of 50 mm / min to obtain the maximum peeling strength.

[0102] 3. Test results

[0103] The test results of this test example are shown in Table 4. From the data shown in Table 4, it can be seen that among the test objects, Comparative Example 1 is insufficient in cycle performance, battery rate performance and positive electrode sheet peeling force, and the test object provided by Comparative Example 2 cannot pass the safety performance test of this test, and also shows obvious deficiencies in cycle performance and rate performance. In this test example, the carbon-coated insulating layer of the carbon-coated current collectors prepared in Example 1, each treatment group of Example 2, each treatment group of Example 3, each treatment group of Example 4 and Example 5 is provided with a transition zone composed of a conductive material and inorganic ceramic particles. By setting the transition zone, the partitions composed of different materials can be smoothly transitioned and connected under the premise of maintaining clear partitions between the conductive material and the inorganic ceramic particles. Based on this, the carbon-coated insulating layer is continuously distributed, which avoids the positive electrode active material slurry from seeping through the carbon-coated insulating layer and directly contacting the surface (empty foil area) of the current collector substrate during the subsequent processing of the positive electrode sheet using the composite current collector, thereby promoting the uniform compounding between the subsequently formed positive electrode active coating and the carbon-coated current collector, thereby improving the overall peeling force between the positive electrode active coating and the carbon-coated current collector, and also improving other performance indicators of the positive electrode sheet.

[0104] Based on the transition zone set on the carbon-coated insulating layer of the composite current collector prepared in Example 5, in the pole piece further prepared in Example 5, the transition zone of the carbon-coated insulating layer is in contact with the surface of the current collector substrate with a second region composed of inorganic ceramic particles, and is in contact with the positive electrode active coating with a first region composed of conductive material, which constitutes a relatively obvious difference from other embodiments. Based on the above differences, the test object provided in Example 5 performs slightly worse than the test objects provided by most of the treatment groups in other embodiments in the tests of positive electrode sheet peeling force, battery cycle performance and battery rate performance. Taking Example 1 as an example, Example 1 is compared with Example 5. In the composite current collector prepared in Example 1, the transition zone in the carbon-coated insulating layer is directly compounded with the current collector substrate with the first region containing conductive particles, which is beneficial to improve the interlayer peeling force between the transition zone and the current collector substrate.

[0105] In addition, in the composite current collectors prepared in Examples 1-4, the first region and the second region constituting the transition zone provided on the composite current collector are composited at a certain tilt angle, which is conducive to increasing the contact area between the first region and the second region, thereby improving the interfacial bonding force between the two, promoting the stable composite of the two, and thereby improving the structural stability of the transition zone and the carbon-coated current collector. Further, by further optimizing the tilt angle of the composite surface of the first region and the second region, the product performance of the positive electrode sheet and the lithium-ion battery using the composite current collector can be further improved. By comparing the test results of each treatment group of Example 1 and Example 2, it can be known that when the tilt angle of the interface where the first region and the second region contact each other in the transition zone of the composite current collector relative to the surface of the current collector substrate reaches 1°-10°, the electrode sheet peeling force of the positive electrode sheet using the composite current collector is higher, and in the transition zone of these composite current collectors, the mutual adhesion between the first region and the second region is high, and the composite interface stability between the first region and the second region is enhanced.

[0106] In addition, the particle size ratio of the conductive particles and the inorganic insulating particles constituting the first region will also affect the electrode peeling force of the positive electrode sheet using the composite current collector. By comparing the actual recording groups 1-4 of Example 1 and Example 4: in the selection of raw materials for preparing the carbon-coated insulating layer of the composite current collector, the particle size ratio of the conductive particles and the inorganic insulating particles selected by the treatment groups 1 and 2 of Example 1 and Example 4 all fall within the range of 1: (0.4-0.8), while the conductive particles and the inorganic insulating particles used by the treatment groups 3 and 4 of Example 4 do not meet the above characteristics; from the test results, the product performance measured by the test objects provided by Example 1, Example 4 treatment group 1, and Example 4 treatment group 2 is better. By comparing Example 1 with each treatment group of Example 2 and Example 4, it can be seen that for the composite current collector provided with a carbon-coated insulating layer, the preferred range of the composite interface inclination angle between the first region and the second region of the transition zone in the carbon-coated insulating layer and the preferred range of the particle size of the conductive particles and the inorganic insulating particles constituting the transition zone. However, by comparing the results of each treatment group of Example 1 and Example 3, the results show that when the inclination angle of the composite interface between the first region and the second region of the transition zone reaches the preferred angle range, and further making the particle size of the conductive particles and the inorganic insulating particles constituting the transition zone within the preferred range, the positive electrode sheet peeling force, battery cycle performance and rate performance of the composite current collector can be particularly significantly improved. This shows that for the above-mentioned product characteristics, when the inclination angle of the composite interface between the first region and the second region of the transition zone reaches the preferred angle range, and the particle size of the conductive particles and the inorganic insulating particles constituting the transition zone is within the preferred range, a synergistic effect can be achieved.

[0107] Table 4. Test results statistics of test objects

[0108]

[0109]

[0110] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. A carbon-coated current collector, characterized in that: The carbon-coated current collector comprises a current collector substrate and a carbon-coated insulating layer, wherein the carbon-coated insulating layer is arranged on the surface of the current collector substrate, the carbon-coated insulating layer comprises an insulating region, a transition region and a conductive region, the material constituting the insulating region comprises inorganic insulating particles, the material constituting the conductive region comprises conductive particles, and the material constituting the transition region comprises inorganic insulating particles and conductive particles; In the width direction of the carbon-coated insulating layer, the insulating region, the transition region, and the conductive region are arranged in sequence, the insulating region and the conductive region are connected through the transition region, and the insulating region is distributed on at least one side edge of the carbon-coated insulating layer in the width direction.

2. The carbon-coated current collector according to claim 1, characterized in that: The transition zone includes a first region and a second region stacked in layers, the material constituting the first region includes conductive particles, the material constituting the second region includes inorganic insulating particles, and the bottom surface of the first region of the transition zone is in contact with the surface of the current collector substrate; Preferably, the conductive particles are one or more of conductive carbon black, graphite, acetylene black, carbon nanotubes, doped carbon nanotubes, carbon fibers, graphene, silver particles, gold particles, copper particles, and aluminum particles, and the inorganic insulating particles are one or more of aluminum oxide, boehmite, calcium oxide, silicon carbide, silicon dioxide, aluminum oxide, boron nitride, magnesium oxide, zirconium oxide, and barium titanate.

3. The carbon-coated current collector according to claim 2, characterized in that: In the carbon-coated insulating layer, the thickness of the first region tends to decrease in the direction away from the conductive region, and the thickness of the second region tends to increase in the direction away from the conductive region. Preferably, the inclination angle of the interface between the first region and the second region relative to the surface of the current collector substrate is 1°-10°.

4. The carbon-coated current collector according to claim 1, characterized in that: The average particle size D of the inorganic insulating particles included in the carbon-coated insulating layer is 50 =0.1μm-5μm, the average particle size D of the conductive particles included in the carbon-coated insulating layer 50 =0.05μm-10μm; Preferably, the average particle size D of the inorganic insulating particles included in the carbon-coated insulating layer 50 =0.6μm-1μm, the average particle size D of the conductive particles included in the carbon-coated insulating layer 50 =0.05μm-2μm.

5. The carbon-coated current collector according to claim 4, characterized in that: The ratio of the average particle size of the conductive particles to the average particle size of the inorganic insulating particles is 1:(0.4-0.8).

6. The carbon-coated current collector according to claim 1, characterized in that: The carbon-coated current collector satisfies at least one of the following conditions: Condition a. In the width direction of the carbon-coated current collector, 0 mm < the width of the transition zone ≤ 10 mm; preferably, the width of the transition zone is 1 mm-10 mm; Condition b. The thickness of the insulating region is 0.5 μm-100 μm; Condition c. The thickness of the transition zone is 0.2 μm-105 μm; Condition d. The thickness of the conductive region is 0.2 μm-5 μm. Condition e: The transition region, the insulating region, and the conductive region have the same thickness.

7. The method for preparing a carbon-coated current collector according to any one of claims 1 to 6, comprising the following operations: S1. coating a conductive material slurry containing the conductive particles on any surface of the current collector substrate; S2. Drying the conductive material slurry to form a conductive material coating; S3. coating an inorganic material slurry containing the inorganic insulating particles on the edge of the conductive material coating along the extension direction of the current collector substrate, and making the inorganic material slurry cover the edge of the conductive material coating and the surface area of ​​the current collector substrate adjacent to the edge; S4. Drying the inorganic material slurry, thereby forming the carbon-coated insulating layer on the surface of the current collector substrate.

8. The preparation method according to claim 7, characterized in that: The S1 also includes the following operations: completing the coating of the conductive material slurry in a zoned coating manner, wherein the corresponding coating area is divided into a main body area and two side edge areas arranged in the width direction of the main body area, and in the process of coating the conductive material slurry, controlling the coating amount of the conductive material slurry so that the coating thickness corresponding to the main body area is greater than the coating thickness corresponding to the edge area.

9. An electrode, characterized in that: The electrode comprises the carbon-coated current collector as claimed in any one of claims 1 to 6 and an electrode active material layer, wherein the electrode active material layer is arranged on the surface of the carbon-coated insulating layer, and the electrode active material layer covers the conductive area.

10. A battery, characterized in that: Comprising the electrode as claimed in claim 9.

Citation Information

Cited By

  • Battery cell, battery device, electric equipment and manufacturing method of battery cell

    CN119764315A